(untitled) (Eurasian Medical Research Periodical, 2022)
The aim of the article is to stimulate the healing of bone defects in the jaws, applying a combined osteoplastic preparation. 72 patients with retained teeth were treated by using combined osteoplastic material. The result of the study is a significant reduction in the number of local complications after bone grafting applying combined osteoplastic drugs